Slight temperature changes cause rapid transcriptomic responses in Trypanosoma cruzi metacyclic trypomastigotes (2020)
Background: Severe changes in temperature can affect the behavior and ecology of some infectious agents. Trypanosoma cruzi is a protozoan that causes Chagas disease. This parasite has high genetic variability and can be divided into six discrete typing units (DTUs). Trypanosoma cruzi also has a complex life-cycle, which includes the process of metacyclogenesis when non-infective epimastigote forms are differentiated into infective metacyclic trypomastigotes (MT). Studies in triatomines have shown that changes in temperature also affect the number and viability of MT. Methods: The objective of this study was to evaluate how temperature affects the transcriptional profiles of T. cruzi I and II (TcI and TcII) MT by exposing parasites to two temperatures (27 °C and 28 °C) and comparing those to normal culture conditions at 26 °C. Subsequently, RNA-seq was conducted and differentially expressed genes were quantified and associated to metabolic pathways. Results: A statistically significant difference was observed in the number of MT between the temperatures evaluated and the control, TcII DTU was not strongly affected to exposure to high temperatures compared to TcI. Similar results were found when we analyzed gene expression in this DTU, with the greatest number of differentially expressed genes being observed at 28 °C, which could indicate a dysregulation of different signaling pathways under this temperature. Chromosome analysis indicated that chromosome 1 harbored the highest number of changes for both DTUs for all thermal treatments. Finally, gene ontology (GO) analyses showed a decrease in the coding RNAs involved in the regulation of processes related to the metabolism of lipids and carbohydrates, the evasion of oxidative stress, and proteolysis and phosphorylation processes, and a decrease in RNAs coding to ribosomal proteins in TcI and TcII, along with an increase in the expression of surface metalloprotease GP63 in TcII. Conclusions: Slight temperature shifts lead to increased cell death of metacyclic trypomastigotes because of the deregulation of gene expression of different processes essential for the TcI and TcII DTUs of T. cruzi.[Figure not available: see fulltext.] © 2020 The Author(s).